(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
We are on FM Distillation, ion exchange, osmosis, medicine used for the preparation of refined products we controlled the water Refined and for injection The water used is an odorless, tasteless, colorless clear liquid and the amount of dry residues, reducing agents, carbon dioxide, nitrates and nitrites, ammonia, chlorides, calcium,it is free of sulfates and heavy metals, and we are one we learned as a result of how many reactions.